An energy-based analysis framework for soil structure interaction systems. (June 2022) - Yang, Han; Wang, Hexiang; Jeremić, Boris
Highlights: Energy based analysis and design framework for soil-structure systems. Thermodynamics based. Comprehensive analysis and design approach for soil-structure systems. Abstract: Presented is an energy-based analysis and design framework for soil structure interaction system. Theoretical formulation based on thermodynamics and engineering mechanics for calculating energy dissipation in soil and structural elastic plastic finite elements is presented and discussed. The importance of incorporation of plastic free energy, that ensures nonnegative incremental energy dissipation, also known as the second law of thermodynamics, is emphasized. For application to practical engineering problems, the presented framework is implemented in the Real-ESSI Simulator and visualized using ParaView. In order to illustrate the proposed framework, a practical model composed of a reinforced concrete frame structure, underlying soil, and soil-foundation interface is developed and analyzed. Elastic-plastic material model and viscous, Rayleigh damping parameters are calibrated to represent typical realistic cases. Spatial and time distribution of energy dissipation density is analyzed and discussed. Locations with high plastic energy dissipation, used as a proxy for material and structural damage are identified. In addition, locations of high plastic energy dissipation within soil and soil-foundation interface, that are used to dissipate seismic energy before it reaches structure, are also identified. Influences of input seismic motion scale and design variation on system performance are investigated. It is shown that traditional displacement-based design parameters, such as peak displacement and maximum interstory drift ratio, could underestimate the change of system performance when different seismic motion scale or structural design are used.